2018
DOI: 10.1088/1361-6528/aac306
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed photoinitiated fabrication of inkjet printed titanium dioxide/reduced graphene oxide nanocomposite thin films

Abstract: This work reports a new technique for scalable and low-temperature processing of nanostructured TiO thin films, allowing for practical manufacturing of TiO-based devices such as perovskite solar cells at low-temperature or on flexible substrates. Dual layers of dense and mesoporous TiO/graphitic oxide nanocomposite films are synthesized simultaneously using inkjet printing and pulsed photonic irradiation. Investigation of process parameters including precursor concentration (10-20 wt%) and exposure fluence (4.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 90 publications
0
3
0
Order By: Relevance
“…Our previous work found that the pulsed light irradiation results in the photoinitiated chemical reaction of the metal-acac molecules for the in situ formation of metal oxidereduced graphitic oxide nanocomposite thin lms. [30][31][32] In this work, it was also found that the Mn-acac precursor absorbs the visible light during the pulsed light irradiation, resulting in the formation of a nanostructured composite thin lm electrode. The rst pulse irradiation produced a sharp and loud sound, possibly because all the Mn-acac molecules transformed into MnO x -reduced graphitic oxide (rGO) aer the absorption of enough light energy.…”
Section: Synthesis Of Highly Porous 3d Nanostructured Manganese Oxidementioning
confidence: 71%
See 1 more Smart Citation
“…Our previous work found that the pulsed light irradiation results in the photoinitiated chemical reaction of the metal-acac molecules for the in situ formation of metal oxidereduced graphitic oxide nanocomposite thin lms. [30][31][32] In this work, it was also found that the Mn-acac precursor absorbs the visible light during the pulsed light irradiation, resulting in the formation of a nanostructured composite thin lm electrode. The rst pulse irradiation produced a sharp and loud sound, possibly because all the Mn-acac molecules transformed into MnO x -reduced graphitic oxide (rGO) aer the absorption of enough light energy.…”
Section: Synthesis Of Highly Porous 3d Nanostructured Manganese Oxidementioning
confidence: 71%
“…Recently, our group reported a unconventional, low-cost and high-throughput pulsed photoinitiated approach to the in situ formation of threedimensional (3D) nanostructured composited thin lm composed of nanocrystalline transition metal oxide and reduced graphitic oxide through ash xenon lamp irradiation of metalorganic precursor lms. [30][31][32] Herein, we report a one-step thin-lm processing method and excellent cyclic stability and ultra-long cycle life of the electrode. Firstly, we have followed a spray-coating technique, which can be accomplished in less than a minute in ambient conditions, to spray Mn-acetylacetonate precursor solution onto the Pt-coated Si substrate.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the performance and stability of lithium-ion batteries and supercapacitors have been shown to be improved by Al 2 O 3 -based nanocomposites [18,19]. Titanium dioxide (TiO 2 ) and its nanocomposites also have notable dielectric properties for a wide range of electronic applications, such as solar cells, gas sensors, and memristors [20][21][22]. In recent times, [23].…”
Section: Experimental Characterization Of Nanomaterials Using Msrmentioning
confidence: 99%